2008
DOI: 10.1016/j.actamat.2008.08.029
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of a general residual stress state on indentation and hardness testing

Abstract: Residual stresses superimpose the stress field from an indentation experiment and do therefore influence the measurement of the volume of interest. The residual stress state can be very different in magnitude and biaxiality and error that may be caused in the measured hardness is difficult to estimate. A prediction of the pressure ratio for stressed and unstressed material is carried out by new model that accounts for nonlinearities caused by the von Mises flow rule. The model can also be used for the correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(55 citation statements)
references
References 27 publications
4
46
1
Order By: Relevance
“…The results of the microhardness measurements indicate the same trend as the residual stress measurement results, in which a slight increase in the microhardness is more pronounced on side 1 ( Figure 5). The increase in the microhardness by around 5% in areas with highest compressive residual stress is in good agreement with the model proposed by Huber and Heerens (2008) [9], assuming that only the uniaxial compressive residual stresses  xx remains present in the cross-sectioned and indented surface. Because the increase in microhardness can be fully attributed to the effect of residual stress, possible contributions from work hardening due to the LSP treatment are insignificant.…”
Section: Figure 5 Residual Stress Profile Measured Using the Hole Drsupporting
confidence: 75%
“…The results of the microhardness measurements indicate the same trend as the residual stress measurement results, in which a slight increase in the microhardness is more pronounced on side 1 ( Figure 5). The increase in the microhardness by around 5% in areas with highest compressive residual stress is in good agreement with the model proposed by Huber and Heerens (2008) [9], assuming that only the uniaxial compressive residual stresses  xx remains present in the cross-sectioned and indented surface. Because the increase in microhardness can be fully attributed to the effect of residual stress, possible contributions from work hardening due to the LSP treatment are insignificant.…”
Section: Figure 5 Residual Stress Profile Measured Using the Hole Drsupporting
confidence: 75%
“…When increasing tensile stress, the hardness rapidly decreases, while the indentation hardness increases with compressive residual stress in a moderate range. That is consistent with the experiments, finite element simulations, and MD simulations [34,35]. However, when the relative compressive residual stress λ is larger than 0.40, the hardness decreases rather than increases as shown in Figure 6, which will be discussed with dislocation evolution in the following subsection.…”
Section: Load Vs Indention Depth Response At Different Residual Stresupporting
confidence: 77%
“…The correlation of the residual stress with the representative hardness has not been attempted since the residual stress measurement is confined only to the nearsurface layers of the coating and thus the peak hardness value is the relevant hardness parameter. It has been shown experimentally as well as by modeling (Ref [33][34][35] that the residual stress present in a material influences the magnitude of its hardness. For example, it has been shown that while hardness decreases with increasing magnitude of tensile residual stress while increasing magnitude of the compressive residual stress causes the hardness to increase ( Ref 33,35).…”
Section: Coating Propertiesmentioning
confidence: 98%
“…It has been shown experimentally as well as by modeling (Ref [33][34][35] that the residual stress present in a material influences the magnitude of its hardness. For example, it has been shown that while hardness decreases with increasing magnitude of tensile residual stress while increasing magnitude of the compressive residual stress causes the hardness to increase ( Ref 33,35). Consistent with the above observations, in this study (Fig.…”
Section: Coating Propertiesmentioning
confidence: 98%